Теоретичні засади страхових і пов'язаних з ними послуг - Коваленко, Юлія Михайлівна; Kovalenko, Yuliia Mykhailivna (Економічний вісник, 2019)
У статті досліджено сутність послуги, її тлумачення у національних і міжнародних нормативно-правових актах. Встановлено, що послуги необхідно визначати та класифікувати відповідно до функціонального призначення фінансового сектору (сектору фінансових корпорацій), де виробляються страхові та пов'язані з ними послуги. Запропоновано класифікацію страхових і пов'язаних з ними послуг за відповідними ознаками. Визначено сутність індустрії страхових і пов'язаних з ними послуг, а також страхової послуги, продукту та комплексу послуг. Запропоновано етапність процесу їхнього впровадження на ринок страхових послуг.

Introduction. Modern changes in the functioning of the financial services market, in particular insurance, are so rapid that they do not always acquire theoretical and methodological reflection and appropriate study. As a result, we now have problems of theoretical, methodological and empirical nature, which affect the further development of insurance business and the full integration of insurance business in the European and world economic space. Purpose. The purpose of the article is to investigate the essence of insurance and related services, to bring them relevant classify cations, as well as offering the author's editorial staff of insurance operations and product. Methods. The basis of the article is the general scientific methods of cognition: systemic; scientific abstraction, analysis and synthesis, functional and system analysis, induction and deduction; method of logical generalization. Results. It has been established that services need to be identified and classified in accordance with the functional load of the financial sector (financial corporations sector), where insurance and related services are performed. Their author's classification is proposed on the basis of features. The essence of the insurance industry and related services, as well as insurance services, products and their complex are determined. The phased process of the irintroduction intermarket of insurance services is off ered. Conclusion. The given classifi cations and characteristics of insurance services, operations and products do not claim to be perfect, due to the rapid development of the insurance services market, as well as in general, the constant changes in the financial market. Regulatory and legal support for the implementation of insurance services in Ukraine needs to be updated in order to bring the international insurance market and the insurance services market into line with international standards, as well as to create an unequivocal legal foundation for their further regulation.
Theoretical bases of insurance services and related them services
Keywords: страхова послуга; страховий продукт; страхова операція; страховик; виробництво; insurance service; insurance product; insurance operation; insurer; production